2014
DOI: 10.1002/hbm.22674
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal neuroimaging evidence of alterations in cortical structure and function in HIV‐infected older adults

Abstract: Combination antiretroviral therapy transformed HIV-infection from a terminal illness to a manageable condition, but these patients remain at a significantly elevated risk of developing cognitive impairments and the mechanisms are not understood. Some previous neuroimaging studies have found hyperactivation in fronto-parietal networks of HIV-infected patients, whereas others reported aberrations restricted to sensory cortices. In this study, we utilize high-resolution structural and neurophysiological imaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 64 publications
9
63
1
Order By: Relevance
“…Our current rs-fc results are in agreement with previous studies by our group that did not observe cortical functional connectivity changes in the SMN due to HIV [16,61]. Of note, recent magnetoencephalography (MEG) studies have showed both structural and functional connectivity loss in the SMN [62,63]. Additional studies are necessary to investigate these discrepancies amongst various imaging modalities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our current rs-fc results are in agreement with previous studies by our group that did not observe cortical functional connectivity changes in the SMN due to HIV [16,61]. Of note, recent magnetoencephalography (MEG) studies have showed both structural and functional connectivity loss in the SMN [62,63]. Additional studies are necessary to investigate these discrepancies amongst various imaging modalities.…”
Section: Discussionsupporting
confidence: 92%
“…With these guidelines in place, it is important to determine the effects of cART on brain functional connectivity. In general, most research groups have found cART to have beneficial effects on cognitive status and neurobiology [28,6366]. While cART may have detrimental effects [65], these do not outweigh the tremendous benefit in restoring overall health and lifestyle [66].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular clinical interest, we computed sensitivity and specificity indices for HAND using the peak amplitude values of the two main MEG findings (i.e., left postcental gyrus and prefrontal cortices) in conjunction, and found that the sensitivity and specificity for HAND were over 85%. 86 These findings strongly suggest that MEG metrics may serve as powerful classifiers in the context of HAND and HIV-associated brain dysfunction. Furthermore, another recent MEG study reported excellent test-retest reliability after ∼24 weeks in both HIV-infected and uninfected participants, 87 which of course is a critical property for any biomarker of disease.…”
Section: Hiv-associated Neurocognitive Disorders (Hand)mentioning
confidence: 87%
“…We found reduced neural responses in the left postcentral gyrus (contralateral to stimulation) shortly after onset of the tactile stimulus in HIV-infected patients, along with increased alpha activity in the prefrontal cortices. 86 HIV-infected patients also had reduced gray matter in parahippocampal, lingual, and other areas, as well as a region of the left postcentral gyrus that spatially coincided with the abnormal MEG response (see Figure 6). 86 This latter finding suggests that some of the functional MEG aberrations observed in HIV disease may reflect alterations in the underlying neural structure, whereas others are more purely functional in nature (e.g., prefrontal cortices).…”
Section: Hiv-associated Neurocognitive Disorders (Hand)mentioning
confidence: 94%
See 1 more Smart Citation